Cadmium tolerance and phytoremediation potential of acacia (Acacia nilotica L.) under salinity stress. Issue 7 (7th June 2018) - Shabir, Rahat; Abbas, Ghulam; Saqib, Muhammad; Shahid, Muhammad; Shah, Ghulam Mustafa; Akram, Muhammad; Niazi, Nabeel Khan; Naeem, Muhammad Asif; Hussain, Munawar; Ashraf, Farah
ABSTRACT: In this study, we explored the effect of salinity on cadmium (Cd) tolerance and phytoremediation potential of Acacia nilotica . Two-month-old uniform plants of A. nilotica were grown in pots contaminated with various levels of Cd (0, 5, 10, and 15 mg kg −1 ), NaCl (0%, 0.5%, 1.0% (hereafter referred as salinity), and all possible combinations of Cd + salinity for a period of six months. Results showed that shoot and root growth, biomass, tissue water content and chlorophyll (chl a, chl b, and total chl a+b) contents decreased more in response to salinity and combination of Cd + salinity compared to Cd alone. Shoot and root K concentrations significantly decreased with increasing soil Cd levels, whereas Na and Cl concentrations were not affected significantly. Shoot and root Cd concentrations, bioconcentration factor (BCF) and translocation factor (TF) increased with increasing soil Cd and Cd + salinity levels. At low level of salinity (0.5%), shoot and root Cd uptake enhanced, while it decreased at high level of salinity (1.0%). Due to Cd tolerance, high shoot biomass and shoot Cd uptake, this tree species has some potential for phytoremediation of Cd from the metal contaminated saline and nonsaline soils.